2008
DOI: 10.4161/psb.3.9.5779
|View full text |Cite
|
Sign up to set email alerts
|

Probing allelochemical biosynthesis in sorghum root hairs

Abstract: Allelopathic interaction between plants is thought to involve the release of phytotoxic allelochemicals by one species, thus inhibiting the growth of neighboring species in competition for limited resources. Sorgoleone represents one of the more potent allelochemicals characterized to date, and its prolific production in root hair cells of Sorghum spp. has made the investigation of its biosynthetic pathway ideally-suited for functional genomics investigations. Through the use of a recently-released EST data se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
56
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(60 citation statements)
references
References 20 publications
1
56
0
3
Order By: Relevance
“…These findings open a range of opportunities for genetic improvement of the germplasm containing this gene, in order to select crops with high allelopathic ability. Despite the great benefit of crops with allelopathic properties for the agroecological management of weeds, scientists emphasize the need to understand the genetic control of allelopathy (Baerson et al 2008b;Albuquerque et al 2010).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…These findings open a range of opportunities for genetic improvement of the germplasm containing this gene, in order to select crops with high allelopathic ability. Despite the great benefit of crops with allelopathic properties for the agroecological management of weeds, scientists emphasize the need to understand the genetic control of allelopathy (Baerson et al 2008b;Albuquerque et al 2010).…”
Section: Resultsmentioning
confidence: 99%
“…According to Marchi et al (2008), sorgoleone is rapidly degraded in soil and is mainly produced in younger plants, its production peaking by 10 days after emergence (DAE). However, other authors have reported that sorgoleone has a long half-life in the soil, with long-term effects on many cellular targets (Dayan et al 2007;Baerson et al 2008aBaerson et al , 2008bBarbosa et al 2010). …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations